К интерпретации мангупской надписи гекатонтарха (?) Тцитс... - Степаненко, В.П. (Материалы по археологии, истории и этнографии Таврии, 2008)
В 1890 г. Ф.А. Браун обнаружил в кладке башни крепостной стены Ман- гупа обломок мраморной плиты с греческой надписью. Надпись была издана по прорисовке, интерпретирована В.В. Латышевым и переиздана Н.В. Малицким. В интерпретации В.В. Латышева надпись гласит; «По(строена эта башня от основания трудом и иждивением) Тцит(цикия гека)тонтарха в правление Тохтам(ыша)». In 1890 F. A. Brown found a fragment of a marble plate with a part of Greek inscription in the laying of a tower of a fortress wall of Mangup. The place of find gave V. V. Latyshev an opportunity to connect the inscription with building the main defense line of Feodoro as a considerable part of bond of the tower was done with secondary used blocks of basilica situated not far from it. So, it is more logical to connect the inscription with the basilica, not with the fortress wall. The larger part of the text was reconstructed by V. V. Latyshev. In particular, neither the name of a builder nor his title of Gekatontarch (?) was preserved; their recovery is highly hypothetic. The same title in the inscription of Khuitanis 1361 /62 is hypothetic too; it was also found in the secondary use in basilica. In general, it can stated that epigraphic monuments with the provenance in Mangup and from the territory of Feodoro principality (funa inscription) can hardly be interpreted unambiguously because they were found not in situ, due to poor preservation, and because their authors backed out from the norms of literary language.